Effect of treatment with exenatide and pioglitazone or basal-bolus insulin on diabetic neuropathy: a substudy of the Qatar Study. Issue 1 (23rd June 2020) - Ponirakis, Georgios; Abdul-Ghani, Muhammad A; Jayyousi, Amin; Almuhannadi, Hamad; Petropoulos, Ioannis N; Khan, Adnan; Gad, Hoda; Migahid, Osama; Megahed, Ayman; DeFronzo, Ralph; Mahfoud, Ziyad; Hassan, Mona; et al.
Abstract : Introduction: To assess the effect of exenatide and pioglitazone or basal-bolus insulin on diabetic peripheral neuropathy (DPN) in patients with poorly controlled type 2 diabetes (T2D). Research design and methods: This is a substudy of the Qatar Study, an open-label, randomized controlled trial. 38 subjects with poorly controlled T2D were studied at baseline and 1-year follow-up and 18 control subjects were assessed at baseline only. A combination of exenatide (2 mg/week) and pioglitazone (30 mg/day) or glargine with aspart insulin were randomly assigned to patients to achieve an HbA1c <53 mmol/mol (<7%). DPN was assessed with corneal confocal microscopy (CCM), DN4, vibration perception and sudomotor function. Results: Subjects with T2D had reduced corneal nerves, but other DPN measures were comparable with the control group. In the combination treatment arm (n=21), HbA1c decreased by 35.2 mmol/mol (3.8 %) (p<0.0001), body weight increased by 5.6 kg (p<0.0001), corneal nerve branch density increased (p<0.05), vibration perception worsened (p<0.05), and DN4 and sudomotor function showed no change. In the insulin treatment arm, HbA1c decreased by 28.7 mmol/mol (2.7 %) (p<0.0001), body weight increased by 4.6 kg (p<0.01), corneal nerve branch density and fiber length increased (p≤0.01), vibration perception improved (p<0.01), and DN4 and sudomotor function showed no change. There was no association between the change in CCM measures with change in HbA1c, weight or lipids. Conclusions: Treatment with exenatide and pioglitazone or basal-bolus insulin results in corneal nerve regeneration, but no change in neuropathic symptoms or sudomotor function over 1 year.